2021
DOI: 10.1007/s00464-021-08785-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender benefit in laparoscopic surgical performance using a 3D-display system: data from a randomized cross-over trial

Abstract: Background The use of 3D technique compared to high-resolution 2D-4K-display technique has been shown to optimize spatial orientation and surgical performance in laparoscopic surgery. Since women make up an increasing amount of medical students and surgeons, this study was designed to investigate whether one gender has a greater benefit from using a 3D compared to a 4K-display system. Methods In a randomized cross-over trial, the surgical performance of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 51 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Four of the included studies were randomized control trials [ 17 , 18 , 20 , 31 ]; in these articles results relating to biological sex or anthropometry were secondary outcomes. The MMAT focuses on the randomization process, initial comparability, blinding, compliance, and completeness of results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of the included studies were randomized control trials [ 17 , 18 , 20 , 31 ]; in these articles results relating to biological sex or anthropometry were secondary outcomes. The MMAT focuses on the randomization process, initial comparability, blinding, compliance, and completeness of results.…”
Section: Resultsmentioning
confidence: 99%
“…The MMAT focuses on the randomization process, initial comparability, blinding, compliance, and completeness of results. Regarding randomization, one study reported using the permuted block technique [ 17 ]; other studies made more general comments about using an independent researcher [ 18 ] or computer randomization [ 31 ]. Following randomization, resulting groups were balanced regarding biological sex in three articles [ 17 , 20 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the male:female ratio between the specialty groups was considerably different, probably reflecting the relevant population in each specialty. Although evidence points to lack of differences between male and female surgeons,40 41 future studies should aim to equate the participants based on sex, to alleviate any concerns around grouping male and female surgeons together.…”
Section: Discussionmentioning
confidence: 99%